Water Quality Assessment in Hong Xeng Channel, Vientiane Capital - Siharath, Phoummixay; Vilaychaleun, Somchay; Thammathevo, Khampasith; Sonemanivong, Chankhachone; Kannitha, Soulyphan; Nhaovarath, Phetsakhone; Keokhamphui, Keoduangchai (Journal of World Science, 2023)
In the capital Vientiane, households, communities and factories discharge wastewater into the Hong Xeng canal, which flows into the Thatluang wetland, where it ends up in the Mak Heiw stream and falls into the Mekong River. Water quality assessment is an excellent factor in indicating the existing water condition. Therefore, the aim of this study was to investigate and collect water samples at 3 locations (P1, P2, and P3) to understand the status of water quality, and analyze 12 water samples of the Hong Xeng Canal and also compare the findings with past data by standard. Methods Data was collected and analyzed in the laboratory for two months from 25 August 2008 to 6 October 2008. The results showed that the temperature was 28°C - 31.1°C, Nitrate ion (NO3-) was 3.2 mg/l - 46 mg/l, pH 5.9-6.6, electrical conductivity 87 µS/cm - 283 µS/cm, Total Suspended Solid (TSS) 22 mg/l -78 mg/l and CODMn 5.5 mg/l - 10 ,9mg/l. Therefore, these parameters are recognized and substandard. While turbidity was 42 NTU -78 NTU, BOD5 4.5 mg/l - 9.1 mg/l, Dissolved Oxygen (DO) 9.1 mg/l - 10.6 mg/l and Phosphate (PO43-) 0.05 mg/l - 0.25 mg/l. this parameter is higher concentration and above standard.